African dreams: locating urban infrastructure in the 2030 sustainable developmental agenda. Issue 2 (4th May 2018) - Pieterse, Edgar; Parnell, Susan; Haysom, Gareth
ABSTRACT: This paper examines African urban infrastructure and service delivery as an entry point for connecting African aspirations with the harsh developmental imperatives of urban management, creating a dialogue between scholarly knowledge and sustainable development policy aspirations. We note a shift to multi-nodal urban governance and highlight the significance of the synthesis of social, economic and ecological values in a normative vision of what an African metropolis might aspire to by 2030. The sustainable development vision provides a useful stimulus for Africa's urban poly-crisis, demanding fresh interdisciplinary and normatively explicit thinking, grounded in a practical and realistic understanding of Africa's infrastructure and governance challenges.